Measuring the flow properties of small powder samples using an avalanche tester. Issue 6 (25th April 2016) - Jaggi, V.; Leaper, M. C.; Ingham, A.
ABSTRACT: The feasibility of using a small-scale avalanche tester to measure the flow properties of pharmaceutical lactose powders was examined. The modes of behavior observed in larger systems were displayed and showed a clear distinction between angular, free-flowing particles and more spherical particles of similar flow characteristics. Angular Lactohale LH100 particles showed slumping behavior at a rotational frequency of 0.33 Hz that disappeared at higher frequencies. Spherical lactose powder with a similar flow function to LH100 only showed rolling behavior under the same conditions, as did more cohesive powders LH200 and LH300. Further investigation of the LH100 data using fast Fourier analysis showed that the slumping frequency was one tenth of the rotational frequency.